Protection of Young People from Information and Psychological Attacks - Nodira, Sherboyeva (European Journal of Life Safety and Stability (2660-9630), 2022)
This article examines the importance of protecting young people from information attacks and the formation of psychological immunity in the process, so that each age is able to understand the essence of a particular skill and knowledge, both religious and secular sciences.